Pemetaan Pemanfaatan Lahan Pertanian Menjadi Lahan Terbangun di Kota Padang Panjang - Rafli Aroyan; Dwi Arini; Fajrin Fajrin; Dwi Marsiska Driptufany (Politeknik Kampar, 2025)
This study aims to map the conversion of agricultural land into built-up areas in Padang Panjang City during the period 2019 to 2025. The transformation of agricultural land into built-up areas is driven by urbanization, population growth, and infrastructure development. The research method employed is spatial analysis based on Geographic Information Systems (GIS) and remote sensing, utilizing Landsat 8 and 9 satellite imagery processed using the supervised classification method and overlay analysis. The results indicate a significant decrease in paddy fields from 817.156 ha in 2019 to 562.264 ha in 2025, while residential areas increased from 414.442 ha to 702.863 ha over the same period. Accuracy assessment using the Confusion Matrix method yielded an overall accuracy of 92% with a Kappa coefficient of 0.85, categorized as very good. The study concludes that there is a significant conversion of agricultural land into built-up areas, highlighting the need for land-use control policies to prevent negative impacts on food security and environmental sustainability.